2015
DOI: 10.1063/1.4922872
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, elastic and electromagnetic properties of epoxy-graphite composites

Abstract: A set of epoxy resin-based composites filled with 0.25 – 2.0 wt.% of commercially available exfoliated graphite (EG) and thick graphene (TG), prepared by suspending EG particles in cyclohexane, and submitting the suspension to a series of grinding and ultrasonic dispersion steps, was produced. The microstructure of such epoxy-graphite composites has been studied by the impulse acoustic microscopy technique. According to acoustic microscopy data, exfoliated graphite microparticles have been well dispersed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…The images are formed in an ultramicroscopic mode —sizes of some scatterers could be smaller than the wavelength; the presence of air in the conglomerates results in a high efficiency of ultrasonic scattering; according to estimations , conglomerates are effective scatterers. It has been revealed that both graphite nanoparticles (GNP) and nanotubes (MWCNT) possess a strong tendency to agglomeration . Depending on the filler content these agglomerates are formed and distributed over the material bulk.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The images are formed in an ultramicroscopic mode —sizes of some scatterers could be smaller than the wavelength; the presence of air in the conglomerates results in a high efficiency of ultrasonic scattering; according to estimations , conglomerates are effective scatterers. It has been revealed that both graphite nanoparticles (GNP) and nanotubes (MWCNT) possess a strong tendency to agglomeration . Depending on the filler content these agglomerates are formed and distributed over the material bulk.…”
Section: Resultsmentioning
confidence: 99%
“…Impulse acoustic microscopy is based on using focused ultrasonic beams and the raster principle of image formation . A focused ultrasonic beam interacts with a plane‐parallel object within its waist.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphene, a two-dimensional (2D) monolayer nanomaterial, has attracted significant attention in recent decades because of its unique electronic, thermal, and mechanical properties, and it is considered to have promising applications in the fields of nano-electronics, [1][2][3][4] flexible/stretchable electronics, 5,6 and nanocomposites, [7][8][9] etc. In graphene-based stretchable electronics and graphenereinforced nanocomposites, the interfacial failures between graphene and substrate materials is the main factor limiting their overall performance and reliability.…”
Section: Introductionmentioning
confidence: 99%